I believe the answer is a trapezoid.
Hope this helps!
-Payshence xoxo
Answer:
parallel I think
Step-by-step explanation:
move the x to the left and divide by y to simplify. the new equation for the bottom will be y=-2x+5. For it to be parallel they have to have the same slope
Answer:
x² - 3x + 5 - [24÷(x+3)]
Step-by-step explanation:
1. Expand (x³ + 2x - 6x - 9)
= x³ - 4x - 9
2. Divide [x³ - 4x - 9 by x+3]
= x² + [(-3x^2-4x-9) ÷ (x+3)]
3. Divide [(-3x^2-4x-9) by (x+3)]
= -3x + [(5x-9) ÷ (x+3)]
x² - 3x + [(5x-9) ÷ (x+3)]
4. Divide [(5x-9) ÷ (x+3)]
= 5 + [(-24) ÷ (x+3)]
x² - 3x + 5 + [(-24) ÷ (x+3)]
= x² - 3x + 5 - [24 ÷ (x+3)]
Answer:
x=47, y=68
Step-by-step explanation:
Add the two equations. Then we get
-y=-68
y=68
Substituting the value of y in the first equation,
8x-6(68)=-32
8x-408=-32
8x=376
x=47
Answer:your answer to this prob,problem, is c) $108.75
Step-by-step explanation: